PELAKSANAAN PERATURAN DESA MEKONG NOMOR 02 TAHUN 2017 TENTANG PEMBENTUKAN BADAN USAHA MILIK DESA LESTARI DI DESA MEKONG KECAMATAN TEBING TINGGI BARAT KEBUPATEN KEPULAUAN MERANTI TAHUN 2019 - Rian Kurnia; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The establishment of village-owned enterprises is based on Law No. 6 of 2014 concerning villages, as well as Government Regulation No. 43 of 2014 concerning Implementing Regulations of Law No. 6 of 2014 concerning Villages. The Meranti Islands Regency Government mandates that every Village Government establish a Village-Owned Business Entity which is listed in Regent Regulation No. 33 of 2017 concerning Implementation Guidelines for Village/Kelurahan BUM. Mekong Village Regulation No. 02 of 2017 concerning the Establishment of Sustainable BUMDes (BUM Desa) Mekong Village has not been fully implemented in accordance with the mandate, such as multiple directors, establishment of business units not through village consultations, BUMDes Lestari has not been able to maximize village potential and lack of human resources in management BUMDes. The formulation of this research is